Image Processing and Communications Challenges 5 - S. Choraś, Ryszard (Advances in Intelligent Systems and Computing, 2014)
This textbook collects a series of research papers in the area of Image Processing and Communications which not only introduce a summary of current technology but also give an outlook of potential feature problems in this area. The key objective of the book is to provide a collection of comprehensive references on some recent theoretical development as well as novel applications in image processing and communications. The book is divided into two parts. Part I deals with image processing. A comprehensive survey of different methods  of image processing, computer vision  is also presented. Part II deals with the telecommunications networks and computer networks. Applications in these areas are considered. In conclusion, the edited book comprises papers on diverse aspects of image processing  and communications systems. There are theoretical aspects as well as application papers.